Pancreatic insulinoma causing hypoglycemic episodes - Moaffaq Mahdi; Bassel Almehman; Safi Nassan; Soliman Binyahib (Elsevier, 2020)
Background: Insulinoma typically has non-specific neuroglycopenic symptoms. It is a neuroendocrine tumor of the pancreas, and leads to recurring hypoglycemic attacks stemming from insulin hypersecretion. Purpose: We report the case of an 8-year-old boy who was diagnosed with insulinoma following referral to our hospital for recurrent hypoglycemic attacks. Results: Abdominal computed tomography scan revealed a lesion at the tail of the pancreas. He tested negative for MEN1 (multiple endocrine neoplasia type 1) syndrome. We performed laparoscopic enucleation of the tumor, and he was discharged home 3 days post-operation with normal blood sugar levels. Five years on, there has been no recurrence of hypoglycemic attacks. Conclusion: Insulinoma is one of the important causes of hypoglycemia in a pediatric age group. Surgery is the mainstay of treatment of insulinoma. Pre-operative localization can be achieved mostly by a single modality, or otherwise multiple modalities in other cases. Minimally invasive enucleation of insulinoma in a pediatric age group is safe and feasible for selective cases, which can preserve normal pancreatic tissue without increasing postoperative complications.